Sekolah Lapang Iklim di RW 13 Kelurahan Umban Sari Kecamatan Rumbai Kota Pekanbaru - Hernimawati Hernimawati; Surya Dailiati; Sudaryanto Sudaryanto (Asosiasi Dosen Akuntansi Indonesia, 2022)
The Climate Field School (SLI) is a learning program for the community so as to improve the ability to make appropriate adjustments and adaptations to deal with extreme weather and climate risks. RW 13, Rumbai Subdistrict, Pekanbaru City has a commitment to be involved in the Climate Field School and Climate Village Program, but not all people understand it, so an approach is needed. As a result, with the involvement of lecturers and students, the community gave a positive response. This is evidenced by their involvement in the program.